Traveler, There Is No Road : Theatre, the Spanish Civil War, and the Decolonial Imagination in the Americas - Jackson-Schebetta, Lisa, 1976- (Book collections on Project MUSE., 2017)
"Traveler, There Is No Road offers a compelling and complex vision of the decolonial imagination in the United States from 1931 to 1943 and beyond. By examining the ways in which the war of interpretation that accompanied the Spanish Civil War (1936-1939) circulated through Spanish and English language theatre and performance in the United States, Lisa Jackson-Schebetta demonstrates that these works offered alternative histories that challenged the racial, gender, and national orthodoxies of modernity and coloniality. Jackson-Schebetta shows how performance in the US used histories of American empires, Islamic legacies, and African and Atlantic trades to fight against not only fascism and imperialism in the 1930s and 1940s, but modernity and coloniality itself. This book offers a unique perspective on 1930s theatre and performance, encompassing the theatrical work of the Cuban, Puerto Rican, and Spanish diasporas in the United States, as well as the better-known Anglophone communities. Jackson-Schebetta situates well-known figures, such as Langston Hughes and Clifford Odets, alongside lesser-known ones, such as Erasmo Vando, Franca de Armiño, and Manuel Aparicio. The milicianas, female soldiers of the Spanish Republic, stride on stage alongside the male fighters of the Lincoln Brigade. They and many others used the multiple visions of Spain forged during the civil war to foment decolonial practices across the pasts, presents, and futures of the Americas. Traveler conclusively demonstrates that theatre and performance scholars must position US performances within the Americas writ broadly, and in doing so they must recognize the centrality of the hemisphere's longest-lived colonial power, Spain"--